Penerapan Metode Pembelajaran Kontekstual dengan pendekatan SCL untuk meningkatkan hasil belajar mahasiswa - Muhammad Nasir Malik; Hasanah Hasanah (Seminar Nasional LP2M UNM, 2019)
This study aims to determine (a) the average value of the engineering physics course in the control class for students of Electrical Engineering Education Study Program Faculty of Engineering Makassar State University, (b) the average value of the physics engineering course in the experimental class for students of Electrical Engineering Education Study Program Faculty of Engineering Makassar State University, and (c) the effectiveness of the contextual learning method with the student-centered learning approach to improve student learning outcomes of the Electrical Engineering Education Study Program at The Faculty of Engineering Makassar State University. The type of research used in this study was quasi experiment research using a descriptive approach. The populations in this study were all electrical engineering education study program students who programed the 2018/2019 odd semester engineering physics course, while the samples were taken proportionally random samples. The research sample was taken proportionally random sample divided into two, namely the experimental class (with treatment) and the control class (without treatment). The results of this study are: (a) the mean value of learning outcomes in the physics engineering course in the control group at 57.67 (pretest) and 66.53 (posttest), (b) the mean value of the learning outcomes of the experimental physics engineering course at 57.74 (pretest) and 79.68 (posttest), and (c) the contextual learning method with the student-centered learning approach is effectively used to improve student learning outcomes of the Electrical Engineering Education Study Program Faculty of Engineering Makassar State University